The Abscopal Effects of Cranial Irradiation Induce Testicular Damage in Mice - Guo, Ling; Qin, Tong-Zhou; Liu, Li-Yuan; Lai, Pan-Pan; Xue, Yi-Zhe; Jing, Yun-Tao; Zhang, Wei; Li, Wei; Li, Jing; Ding, Gui-Rong (Frontiers in Physiology, 2021)
To investigate whether the abscopal effects of cranial irradiation (C-irradiation) cause testicular damage in mice, male C57BL/6 mice (9weeks of age) were randomly divided into a sham irradiation group, a shielded group and a C-irradiation group and administered sham/shielded irradiation or C-irradiation at a dose rate of 2.33Gy/min (5Gy/d for 4 d consecutively). All mice were sacrificed at 4weeks after C-irradiation. We calculated the testis index, observed testicular histology by haematoxylin-eosin (HE) staining and observed testicular ultrastructure by transmission electron microscopy. Western blotting was used to determine the protein levels of Bax, Bcl-2, Cleaved caspase 3, glial cell line-derived neurotrophic factor (GDNF) and stem cell factor (SCF) in the testes of mice. Immunofluorescence staining was performed to detect the expression of Cleaved caspase 3 and 3β hydroxysteroid dehydrogenase (3βHSD), and a TUNEL assay was used to confirm the location of apoptotic cells. The levels of testosterone (T), GDNF and SCF were measured by ELISA. We also evaluated the sperm quality in the cauda epididymides by measuring the sperm count, abnormality, survival rate and apoptosis rate. The results showed that there was no significant difference in testicular histology, ultrastructure or sperm quality between the shielded group and sham group. Compared with the sham/shielded group, the C-irradiation group exhibited a lower testis index and severely damaged testicular histology and ultrastructure at 4weeks after C-irradiation. The levels of apoptosis in the testes increased markedly in the C-irradiation group, especially in spermatogonial stem cells. The levels of serum T and testicular 3βHSD did not obviously differ between the sham group and the C-irradiation group, but the levels of GDNF and SCF in the testes increased in the C-irradiation group, compared with the sham group. In addition, the sperm count and survival rate decreased in the C-irradiation group, while the abnormality and apoptosis rate increased. Under these experimental conditions, the abscopal effects of C-irradiation induced testicular damage with regard to both structure and function and ultimately decreased sperm quality in mice. These findings provide novel insights into prevention and treatment targets for male reproductive damage induced by C-irradiation.